Oritavancin for the treatment of complicated gram-positive infection in persons who inject drugs - Aileen Ahiskali; Heather Rhodes (BMC, 2020)
Abstract Background Treatment of complicated infections in persons who inject drugs (PWID) and patients experiencing homelessness poses a unique challenge to clinicians. Long-acting lipoglycopeptide antibiotics, such as oritavancin, may facilitate extended courses of outpatient intravenous therapy while avoiding the need for central lines, improving compliance and thus increasing the chance of clinical cure. Methods Retrospective chart review of adult PWID who received at least one dose of oritavancin for a gram-positive infection between 1/1/17 and 6/30/19 at a large safety net hospital. Results Twenty three PWID received 24 courses of at least one dose of oritavancin for a gram-positive infection; 16 were experiencing homelessness at the time of diagnosis. Methicillin resistant Staphylococcus aureus (MRSA) was the most common infecting pathogen and bone or joint the most frequent infection site. Nineteen encounters resulted in clinical cure, including 5 whose conditions improved despite non-adherence to their prescribed regimen. Three patients experienced a non-favorable outcome. Two patients experienced mild adverse drug reactions that did not interfere with therapy; no patients died while on therapy. Conclusion Oritavancin may be a clinically effective treatment option for the management of complicated gram-positive infections in PWID and patients experiencing homelessness. Further studies should be performed to validate these results.